THE EFFECTIVENESS OF USING WHOLE BRAIN TEACHING METHOD IN THE TEACHING OF SPEAKING - Farikha, Ninik (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2024)
Finding out how students communicate both before and after receiving instruction utilizing the whole brain teaching method is the aim of this study. The effectiveness of the whole brain teaching method in the Sibling English Course, as well as the notable difference in students' speaking abilities before and after instruction are both demonstrated. Because the outcome of this study is correlated with a numerical value that is derived quantitatively, a quantitative experimental design was adopted. Students in the foundational class of the Sibling English Course are the focus of this study. There are 20 pupils enrolled. Pre-test, treatment, and post-test were the three phases in the research process. (1) The research's findings indicate that students' speaking before receiving instruction utilizing the whole brain teaching approach falls between the